2015
DOI: 10.3389/fnbeh.2015.00077
|View full text |Cite
|
Sign up to set email alerts
|

Combined neuromodulatory interventions in acute experimental pain: assessment of melatonin and non-invasive brain stimulation

Abstract: Transcranial direct current stimulation (tDCS) and melatonin can effectively treat pain. Given their potentially complementary mechanisms of action, their combination could have a synergistic effect. Thus, we tested the hypothesis that compared to the control condition and melatonin alone, tDCS combined with melatonin would have a greater effect on pain modulatory effect, as assessed by quantitative sensory testing (QST) and by the pain level during the Conditioned Pain Modulation (CPM)-task. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 95 publications
0
19
0
Order By: Relevance
“…Probably, melatonin treatment causes an improvement in rat’s spontaneous running activity because of its antioxidants and ant-inflammatory mechanisms of action, well known melatonin properties [ 47 , 48 , 49 , 50 , 51 ]. Although these beneficial effects are potentially related also to analgesic [ 30 , 52 , 53 , 54 , 55 ] melatonin properties, experimental studies as well as clinical trials in humans have demonstrated that melatonin has an analgesic properties in chronic, acute, inflammatory and neuropathic pain conditions, including fibromyalgia [ 44 , 56 , 57 , 58 ]. Importantly, these effects seem MT2 receptor-mediated, as shown by the group of Granados-Soto describing that selective MT2 receptor partial agonists have analgesic properties through modulation of brainstem descending anti-nociceptive pathways [ 28 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probably, melatonin treatment causes an improvement in rat’s spontaneous running activity because of its antioxidants and ant-inflammatory mechanisms of action, well known melatonin properties [ 47 , 48 , 49 , 50 , 51 ]. Although these beneficial effects are potentially related also to analgesic [ 30 , 52 , 53 , 54 , 55 ] melatonin properties, experimental studies as well as clinical trials in humans have demonstrated that melatonin has an analgesic properties in chronic, acute, inflammatory and neuropathic pain conditions, including fibromyalgia [ 44 , 56 , 57 , 58 ]. Importantly, these effects seem MT2 receptor-mediated, as shown by the group of Granados-Soto describing that selective MT2 receptor partial agonists have analgesic properties through modulation of brainstem descending anti-nociceptive pathways [ 28 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of subjects in each study group was determined by the parameters of a previous survey ( da Silva et al, 2015 ). To achieve 80% power at 1% significance, with a 0.5 variation coefficient, we need a total of 48 subjects divided into four equal groups ( n = 12) in 1:1:1:1 ratio to test 1 point [ Standard deviation ( SD = 2)] mean a difference between groups for the NPS (0–10).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 592 subjects were randomized in thirteen clinical trials involving different chronic pain conditions; 4 in low back pain 26,27,63,64 ; 2 in fibromyalgia 65,66 , 2 in Myofascial Pain Syndrome 67,68 , 1 in chronic visceral pain 69 , 1 in chronic regional pain (CRPS) 70 , 1 in spinal cord injury (SCI) 71 , 1 in general neuropathic pain subjects 72 and 4 ongoing studies. 7377 Most of the studies combined tDCS with a behavioral therapy such as cognitive behavioral training, exercise, visual illusion or with other types of stimulation such as peripheral electrical stimulation (PES) or transcranial pulsed current stimulation (tPCS).…”
Section: Perspectives In Regards Of How To Enhance Tdcs Effectsmentioning
confidence: 99%